Content validity of the Sheehan Irritability Scale in patients with major depressive disorder. (March 2016) - Mannix, Sally; Hassan, Mariam; Tummala, Raj; Locklear, Julie C.; Revicki, Dennis A.; Khan, Sajjad; Dunbar, Geoffrey C.; Eriksson, Hans; Sheehan, David V.
Abstract : The Sheehan Irritability Scale (SIS) measures the frequency, severity, and impairment associated with irritability in psychiatric patients. The content validity of the SIS in patients with major depressive disorder (MDD) has not been evaluated. A cross-sectional, qualitative research study was conducted to assess the content validity of the SIS among patients with MDD. One-on-one interviews were conducted, starting with open-ended questions to evaluate the consistency of the SIS content with patient experiences of irritability. Participants then completed the SIS and cognitive interviews around the comprehension of the SIS content (instructions, items, response options). Participants included 24 patients diagnosed with MDD who had an inadequate response to an antidepressant treatment. The sample was: 50.4 mean years, 66.7% female, and 91.7% white racial background. All concepts on the SIS were spontaneously mentioned by at least one participant, and when probed about the symptoms, the majority of participants (66.7–100%) reported the concepts being part of their experience. The majority of participants (70.8–100%) understood the SIS instructions, items, and response scales. This study provides evidence of content validity of the SIS in patients diagnosed with MDD, supporting the use as a measure of irritability in patients with depression.